The Concept of Paul's Katallage and Hilasmos: Internalization Through Group Counseling for Millennials - Anggi Maringan Hasiholan; Andreas Budi Setyobekti; Robert Paul Trisna (Department of Guidance and Counseling, FIP, Undiksha, 2021)
The Atonement wrought by Jesus Christ is the foundation of the Christian faith that must be held and believed to gain one's salvation. Paul calls this concept with two words Katallage and Hilasmos which means restoring the relationship between God and sinful man to live again to the design that God has ordained. However, this concept rarely gets attention because Christians focus more on Justification. In addition, the atonement made by Jesus is also tricky for the millennial generation to accept in this postmodern era because of the relativism and pluralism spirit contained in it. That is why it is necessary to build the concept of atonement that Jesus did and implement it to the youth. The research method used is a qualitative case study, namely the implementation to the youth of the Ministry of Refreshment, Bekasi. The results showed that the atonement made by Jesus brought a mandate to the younger generation of the Refresh Ministry to glorify God and spread this atonement to others who have not reconciled. This value inculcation carries out a discipleship model that balances teaching and encounter.